Aspectos clínico-patológicos do envenenamento experimental por Caudisona durissa em equinos - LOPES, Cinthia Távora de Albuquerque (Universidade Federal do Pará, 2017)
The clinic-pathological picture and laboratory findings in horses experimentally inoculated with the venom of Caudisona durissa terrificus (Crotalus durissus terrificus, according to the former nomenclature) are described. The purpose of this study was to contribute to the understanding of this type of snake accident in horses. The lyophilized venom was diluted into 1ml of a 0.9% saline solution and was inoculated subcutaneously into five horses, at the doses of 0.12mg/kg (one horse), 0.066mg/kg (two horses) and 0.03mg/kg (two horses). The venom caused death of the horse that had received 0.12mg/kg, and of one horse of the two that had received the dose of 0.066mg/kg. The clinical course varied from 27h27min to 52h29min. The second horse inoculated with 0.066mg/kg recovered within 12 days after inoculation. The dose of 0.03mg/kg had a course of 6 to 10 days but did not cause fatal envenomation. The clinical picture in the horses was characterized by swelling of the inoculation site and adjacent areas, by apathy and lowered head, locomotory alterations shown by dragging of the hoves on the ground, decubitus and difficulty to get up, reduction of auricular, palatal, upperlip and threat reflexes, and increase of heart and breathing frequency. The laboratory examination revealed leukocytosis and lymphocytosis in two horses. There was increase of the creatine-kinase (CK), lactic dehydrogenase (DHL) and ureia; reduction in the seric levels of calcium, phosphorus and magnesium. The time of activated partial tromboplastina (TTPA) increased in the horses that died. Post mortem findings were edema of the subcutaneous tissue at the inoculated shoulder, suffusions in the epicard of left and right heart ventricles, bladder replete with urine containing a white-yellowish sediment, and hemorrhagic areas in its mucosa. Histopatologic examination revealed the liver parenchyma with diffuse moderate vacuolation affecting predominantly the intermediate area of the hepatic lobe, and slight dilation of the sinusoides in some areas; in the kidney slight dilation of the uriniferous tubules mainly in the cortex.